The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/ca.23605
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of the Rouviere's sulcus: A meta‐analysis with implications for laparoscopic cholecystectomy

Abstract: Rouvière's sulcus (RS) is increasingly being recognized as an important extra‐biliary landmark during laparoscopic cholecystectomy (LC). The aim of this study was to conduct a systematic analysis of the prevalence and morphological types of RS. A systematic search was conducted through the major databases PubMed, ScienceDirect, Google Scholar, China National Knowledge Infrastructure (CNKI), SciELO, and the Cochrane Library to identify studies eligible for inclusion. The data were extracted and pooled into a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 44 publications
(82 reference statements)
0
18
2
Order By: Relevance
“…Thapa et al 16 reported visualized Rouviere's sulcus in of 75% of patients, Dahmane et al 8 reported an incidence of 82%, while Peti et al 7 described an incidence of 80%. The highest reported incidence of Rouviere's sulcus (> 90% visualization rate) was reported by Singh et al 12 and Kumar et al 17 In a recent meta-analysis of 23 anatomical or laparoscopic studies, Cheruiyot et al 18 reported an overall incidence of 83%. These minor variations are attributed to different degrees of including the scar type of Rouviere's sulcus in these studies.…”
Section: Discussionmentioning
confidence: 95%
“…Thapa et al 16 reported visualized Rouviere's sulcus in of 75% of patients, Dahmane et al 8 reported an incidence of 82%, while Peti et al 7 described an incidence of 80%. The highest reported incidence of Rouviere's sulcus (> 90% visualization rate) was reported by Singh et al 12 and Kumar et al 17 In a recent meta-analysis of 23 anatomical or laparoscopic studies, Cheruiyot et al 18 reported an overall incidence of 83%. These minor variations are attributed to different degrees of including the scar type of Rouviere's sulcus in these studies.…”
Section: Discussionmentioning
confidence: 95%
“…In this article, we introduced the CATAM rubric and used it to critically appraise a recently published anatomical MA (Kacprzyk et al, 2020). There have been other anatomical MAs recently published (Aldabe et al, 2019; Bellier et al, 2020; Berthaume & Bull, 2021; Cheruiyot et al, 2021; Dreher et al, 2018; Graves et al, 2017; Harvie et al, 2019; Koziej et al, 2020; Morelli et al, 2019; Nallikuzhy et al, 2018; Roberts et al, 2021; Sirico et al, 2019; Solewski et al, 2021; Stefura et al, 2018; Tomaszewska et al, 2018; Tomaszewska et al, 2018; Tomaszewski et al, 2017; Tomaszewski et al, 2017; Vikse et al, 2016a, 2016b; Whitley et al, 2020; Yammine, 2013, 2014b, 2014c, 2014d; Yammine et al, 2015; Yurasakpong et al, 2021). We believe that the running paper that we used is an exemplary anatomical MA (Kacprzyk et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…The sulcus of Rouviere is an established landmark for superior/inferior orientation and identification of the plane of the common bile duct; any dissection below the sulcus may result in BDI [ 3 , 20 , 21 ]. There are three basic forms of this landmark, an open triangle being the most common one with the right portal pedicle mostly present on its floor [ 3 , 21 ].…”
Section: Discussionmentioning
confidence: 99%